Tiger at the Crossroads - Badhwa, Anoop (Indian Forester, 2002)
’Project Tiger’was launched in 1972 when the tiger population was reduced to a meagre 1 ,872 in number. Restorative management measures undertaken in the Project successfully increased its population to 4 ,334 , and it was acclaimed as one of the best managed projects of the world. However , later this could not be sustained and the population fell to 3 ,500 in 1997. The major threats are fragmentation and loss of prime habitat , poaching for commercial trade in tiger parts for medicine and vigour boosters and human-tiger conflict etc. To overcome these restraints the author suggests increase in budgetary allotment for conservation , linking of Protected Areas into a network with dispersal corridors , effective implementation of conservation laws , streamlining of NGO cooperation , ensuring trans-boundary cooperation for conservation , obtaining Centre and State-level political will to contain human-tiger conflict and manage the PAs move effectively , so that the tiger is placed on the path of recovery , and the success of the Project - which is now at a cross-roads - is ensured.